The role of high mobility group box 1 protein (HMGB1) in the immunopathology of experimental pulmonary tuberculosis - Hernández Pando, Rogelio (2015)
Background: The high mobility group box 1 (HMGB1) is the prototype of alarmin protein released by stressed or dying cells. The redox state of this protein confers different functions in the regulation of inflammation and immune response. Aim: Determine the kinetics, cellular sources and function of HMGB1 in experimental tuberculosis. Methods: BALB/c mice were infected with Mycobacterium tuberculosis strain H37Rv. At different time points, HMGB1 was quantified in bronchial lavage fluid (BALF) and in lungs was determined its cellular sources by immunohistochemistry. HMGB1 was blocked with specific antibodies or recombinant HMGB1 was administered during early or late infection. Bacilli burdens, inflammation and cytokines expression were determined. Results: The maximal concentration of HMGB1 in BALF was at day one of infection. Bronchial epithelium and macrophages were the most important sources. At day 7 to 21 the oxidized HMGB1 was predominant, while during late infection only the reduced form was seen. Blocking HMGB1 during early infection produced significant decrease of bacilli burdens and high production of pro-inflammatory cytokines, while the opposite was seen when HMGB1 was administered. Blocking HMGB1 activity or administrated it in high amounts during late infection worsening the disease.